Cell-autonomous megakaryopoiesis associated with polyclonal hematopoiesis in triple-negative essential thrombocythemia - Tadaaki Inano (Nature Portfolio, 2021)
Abstract A subset of essential thrombocythemia (ET) cases are negative for disease-defining mutations on JAK2, MPL, and CALR and defined as triple negative (TN). The lack of recurrent mutations in TN-ET patients makes its pathogenesis ambiguous. Here, we screened 483 patients with suspected ET in a single institution, centrally reviewed bone marrow specimens, and identified 23 TN-ET patients. Analysis of clinical records revealed that TN-ET patients were mostly young female, without a history of thrombosis or progression to secondary myelofibrosis and leukemia. Sequencing analysis and human androgen receptor assays revealed that the majority of TN-ET patients exhibited polyclonal hematopoiesis, suggesting a possibility of reactive thrombocytosis in TN-ET. However, the serum levels of thrombopoietin (TPO) and interleukin-6 in TN-ET patients were not significantly different from those in ET patients with canonical mutations and healthy individuals. Rather, CD34-positive cells from TN-ET patients showed a capacity to form megakaryocytic colonies, even in the absence of TPO. No signs of thrombocytosis were observed before TN-ET development, denying the possibility of hereditary thrombocytosis in TN-ET. Overall, these findings indicate that TN-ET is a distinctive disease entity associated with polyclonal hematopoiesis and is paradoxically caused by hematopoietic stem cells harboring a capacity for cell-autonomous megakaryopoiesis.